Large-scale features of the summer monsoon during 1979 (MAUSAM, 1986)
Monthly mean zonal and medicinal winds are subjected to Fourier analysis for the Monex year 1979 during the months April through August between latitudes 48° Sand 48° N at 700mb and 300mb levels. From these amplitudes and phases, meridional transport of momentum and wave to wave and wave to zonal mean flow interactions have been computed in wave number domain. The results obtained for 1979  (a bad monsoon year) have been compared with similar results obtained by other workers. Mean medicinal circulation is significant for the transport of momentum between latitudes 20° S and 20° N. Convergence of momentum between the equator and 10° N, leads to weak easterlies in 1979 in monsoon months in the upper troposphere. In 1967 there is divergence of momentum. In this region .In 1979, m the tropics, waves 1,3 and 4 are greater source of kinetic energy to other waves via wave-wave interactions and to mean zonal flow The year 1979 shows similarity with 1972 (a bad monsoon year) in respect of energetic and circulation patterns but it shows contrast with 1967 (a good monsoon year).